2016
DOI: 10.5056/jnm16069
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Triggers in Irritable Bowel Syndrome: Is There a Role for Gluten?

Abstract: A tight link exists between dietary factors and irritable bowel syndrome (IBS), one of the most common functional syndromes, characterized by abdominal pain/discomfort, bloating and alternating bowel habits. Amongst the variety of foods potentially evoking "food sensitivity", gluten and other wheat proteins including amylase trypsin inhibitors represent the culprits that recently have drawn the attention of the scientific community. Therefore, a newly emerging condition termed non-celiac gluten sensitivity (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 97 publications
(121 reference statements)
2
66
0
Order By: Relevance
“…As shown in Table 1, anxiety, chronic headache and gastro-intestinal reflux disease were more common in the srGS group compared with controls. These subjective health complaints are also common symptoms in patients with irritable bowel syndrome (IBS) and self-reported food intolerance in general [21,22,23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, anxiety, chronic headache and gastro-intestinal reflux disease were more common in the srGS group compared with controls. These subjective health complaints are also common symptoms in patients with irritable bowel syndrome (IBS) and self-reported food intolerance in general [21,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Foods which are reported to be associated with IBS symptoms are commonly rich in gluten, wheat and carbohydrates [23]. Therefore NCWS could be seen as part of IBS with a gluten-free diet as treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…described chronic diarrhea that improved after a gluten‐free diet (GFD) and was triggered by gluten challenge in subjects without celiac disease. Since then, studies have reported conflicting results leading to a shift in terminology, non‐celiac wheat sensitivity (NCWS), which reflects our uncertainty on the exact trigger and mechanisms involved …”
Section: Introductionmentioning
confidence: 99%
“…Gluten-rich cereals are a valuable source of nutrients in the general diet, so their exclusion could potentially lead to nutritional deficiencies[98]. …”
Section: Gluten/wheat Intake In Ibsmentioning
confidence: 99%